Application of boron-doped diamond, Ti/IrO2, and Ti/Pt anodes for the electrochemical oxidation of landfill leachate biologically pretreated by moving bed biofilm reactor - Arseto Yekti Bagastyo (IWA Publishing, 2021)
Conventional biological treatments used in most Indonesian landfill sites are mostly ineffective in treating stabilized landfill leachates to meet the standard regulation. Thus, a combination of biological and electrochemical process is offered to successfully treat leachates containing a high concentration of organic and nitrogenous compounds. In this study, a moving bed biofilm reactor (MBBR) was applied prior to electrochemical oxidation by using boron-doped diamond (BDD), Ti/IrO2, and Ti/Pt anodes with applied current of 350, 400 and 450 mA. The objectives were to investigate the effect of anode type and the applied current on the removal of organics as well as total nitrogen from the MBBR-treated leachate with electrochemical oxidation. The optimum removal of chemical oxygen demand (COD) observed on the Ti/Pt anode was 78% by applying 400 mA, with an estimated energy of 56.7 Wh g L–1. In the case of Ti/IrO2 and BDD anodes, the optimum removal of COD was 76 and 85% with an energy consumption of 58.9 and 36.9 Wh g L–1, respectively, both achieved at 350 mA. Although all anodes showed less-satisfactory performances for total nitrogen reduction, around 46–95% removal of nitrogenous compounds was achieved by MBBR, with their partial conversion to nitrates. HIGHLIGHTS Real stabilized leachate has been treated by combined MBBR-electrochemical oxidation process.; Sequential removal of nitrogenous and organics compound in the leachate was obtained.; At optimum current applied, 85, 78, and 76% COD removal achieved by BDD, Ti/Pt, and Ti/IrO2 anode.; BDD has the lowest energy consumption of 36.9–55.6 kWh g−1 COD removed at 350–450 mA.;